On the conservation of fungi - A. A. Shirokikh; I. G. Shirokikh (Аграрная наука Евро-Северо-Востока, 2021)
The article is devoted to the actual problem of conservation of biological diversity in the modern world. The basic principles and specific approaches to the protection of macromycetes as organisms that are difficult in qualitative and quantitative accounting due to the peculiarities of biology and life cycle have been studied. Domestic and global trends and practices in the field of protecting the species diversity of agaricoid fungi as a component of any ecosystem are discussed. The information on the features of regional fungal diversity detection, rare and threatened species for inclusion into the Red lists of various levels as well as on determining the boundaries of fungal populations, including using barcoding methods is provided. It is noted that for the organization of specially protected natural areas, it is necessary to specify and substantiate the changes in the status of separate species, to identify key areas with specific and typical mycological complexes. The idea that the system of mushroom protection should be integrated into the general system of nature protection is substantiated. Along with the protection of rare and endangered fungi species in their typical habitats (nature reserves, nature parks, wildlife areas, etc.), priority directions for preserving the gene pool of fungi in scientific collections and ex situ banks are described. Live mycelial cultures of fungi can be used for the development of new resistant populations by the reintroduction of rare and endangered species, as well as for the production of fungal metabolites useful for humans. There has been also discussed the problem of improving the effectiveness of protective measures through the digitalization of information systems: free and open access to the data on the endangered fungi species through the development of specialized computer databases, websites and unified information banks.